Income uncertainty and aggregate consumption - Lorenzo Pozzi (National Bank of Belgium, 2005)
We investigate the relevance of aggregate and consumer-specific income uncertainty for aggregate consumption changes in the US over the period 1952-2001. Theoretically, the effect of income risk on consumption changes is decomposed into an aggregate and into a consumer-specific part. Empirically, aggregate risk is modelled through a GARCH process on aggregate income shocks and individual risk is modelled as an unobserved component and obtained through Kalman filtering. Our results suggest that aggregate income risk explains a negligible fraction of the variance of aggregate consumption changes. A more important part of aggregate consumption changes is explained by the unobserved component. The interpretation of this component as reflecting consumer-specific income risk is supported by the finding that it is negatively affected by received consumer transfers.
Keywords: E21; 330; income uncertainty; consumption; precaution; state space models; GARCH errors; unobserved component; Bayesian.; Einkommen; Risiko; Privater Konsum; ARCH-Modell; Bayes-Statistik; USA